Gault's Promise Revisited: The Search For Due Process. (1st June 2018) - Blitzman, Jay D.
Abstract: Fifty years ago, due process was introduced into the juvenile courts, but today children still do not have the guiding hand of counsel at every stage of the proceedings. In assessing the pre‐ Gault world, Chief Justice Fortas observed that "[a] child receives the worst of both worlds:…he gets neither the protections accorded to adults nor the solicitous care and regenerative treatment postulated for children." Fortas opined that "Then as now good will and compassion were admirably prevalent. But recent studies have entered with surprising unanimity, sharp dissent to the vitality of this gentle conception. They suggest that the appearance as well as the actuality of fairness‐ impartiality and orderliness‐ in short the essentials of due process may be a more therapeutic attitude so far as the juvenile is concerned."2 The prescience of his observation has found resonance and reinforcement with the 2013 publication of Reforming Juvenile Justice: A Developmental Approach3 which was commissioned by the Office of Juvenile Justice Delinquency and Prevention (OJJDP). Reforming Juvenile Justice's emphasis on encouraging not only the perception but the actuality of fairness in all domains4 connects directly to the essence of Gault's message. "Treating youth fairly and ensuring that they perceive that have been treated fairly and with dignity contribute to positive outcomes in the normal processes of social learning, moral development, and legal socialization adolescence."5 The research also demonstrates that public health oriented alternatives to traditional court processing promote social connection and positive youth development.6 The OJJDP report provides a road map for promoting positive youth development and social engagement by demonstrating that supporting such policies improves public safety outcomes by reducing recidivism. In exploring whether Gault's promise of due process has been realized or is still aspirational, this article suggests that our inquiry requires us to think contextually by considering how children and families are treated in and out of the courtroom. This entails consideration of educational, child welfare and mental health services, as well as the scope of legal entitlements. Equity and fundamental fairness, euphemisms for due process, are what will truly effectuate Gault's promise and should be the benchmark for all courts and systems that engage with children.